La AplicaciÃ³n De Herramientas DidÃ¡ctica En El Aula De Clase â€œInteractive Physicsâ€ Y Su Incidencia En El Rendimiento AcadÃ©mico Estudio De Caso: Estudio De Las Leyes De Newton - Arellano, Marco Hjalmar Velasco; Guadalupe, Carla SofÃa Arguello; Guashima, Oswaldo Geovanny MartÃnez; Calle, Carmen Cecilia MejÃa; LeÃ³n, Hugo Humberio Paz (European Scientific Journal, ESJ, 2017)
This research work seeks to find out the incidence that the educative software called Interactive Physics has on the studentsâ€™ academic performance. The experiment will consider students who are studying their first semester in the Agronomy School, classroom â€œ1â€, at the Natural Resources College of ESPOCH. The class will be divided in two subgroups with whom an interactive simulator program will be used and it will allow students to develop skills within the collaborative learning method of Physics, specifically, the Newtonâ€™s Laws. The hypothesis is the following: making and applying the guideline called Dynamic by using the Interactive Physics influences the first semester Agronomy studentsâ€™ academic performance. The above mentioned dynamic guide was used in one of the groups in order to analyze their academic performance. The other group did not use it. Then, through the statistical Chi-Squared test and the Normalized Z-score, the existence of high correlation concerning the studentsâ€™ academic performance when using the didactic guide Interactive Physics was evidenced. As a conclusion it can be said that the use of this methodology improves studentsâ€™ academic performance.